PERFORMANCE EVALUATION OF MEDICINAL AND AROMATIC PLANTS IN HORTI-MEDICINAL AGROFORESTRY SYSTEM UNDER ARID REGIONS OF ANDHRA PRADESH - A , MALLISWARA REDDY (The Journal of Research ANGRAU, 2026)
A field experiment was conducted for evaluation of medicinal and aromatic plants in hortimedicinal agroforestry system under semi-arid regions of Andhra Pradesh during kharif,2021and 2022 at AICRPDA, Agricultural Research Station, Ananthapur. The treatments consist offour main plots (Trees) of size 72X 36 m viz., Simarouba, Custard apple, Jamun and Amla andthree sub plots (Medicinal plants) of size 36 X 4 m viz., Aswagandha, Senna, Nannari and Velvetbean. The experiment was conducted in split plot design with three replications. During 2021,Amla trees, recorded an average fruit yield  of 8.0 kg per tree and Jamun fruit yield was 8 kg pertree. During 2022, Amla trees recorded an average fruit yield of 9.3 kg per tree, jamun averagefruit yield was 7.1 kg per tree and custard apple average fruit yield was 0.7 kg per tree. Thepresent study findings showed that, in semi-arid regions of Andhra Pradesh, all of the testedmedicinal plants performed better when grown as sole crops as compared to different tree-basedintercropping systems. Sub plot treatments viz.,  medicinal plants intercropped in custard appleperformed well (Mean leaf yield of Aswagandha was 1547 kg ha-1 , Aswagandha root dry weightwas 87 kg ha-1 ; Senna leaf dry weight was 1674 kg ha-1  and  velvet bean seed yield was 293 kgha-1 )compared to other trees.